Dialectology and Qiraat: The Existence of al-Ahruf al-Sab'ah in the Study of Ulum al-Quran - Amalia, Rosyida; Budi, Eko Prasetyo; Marzuki, Ahmad (STKQ Al-Hikam Depok, 2025)
The discourse on al-Ahruf as-Sab'ah represents a pivotal theme in the study of Ulum al-Quran, particularly in relation to the diversity of recitations (qiraat) and Arabic dialects. This study aims to explore the existence of al-Ahruf as-Sab'ah within the frameworks of dialectology and qiraat, as well as its implications for Quranic interpretation and Islamic legal derivation. Employing a qualitative-descriptive approach through a literature review method, this research draws upon classical sources such as al-Itqan by al-Suyuti and Jami al-Bayan by al-Tabari, alongside relevant contemporary references. The analysis investigates the concept of ahruf, the historical development of qiraat, and their relationship to variations in Arabic lahjah. The findings suggest that the diversity of Quranic recitations is deeply rooted in the linguistic landscape of the time of revelation and that these variations significantly influence Quranic exegesis and the derivation of Islamic legal rulings (istinbat al-ahkam).